A call to action: mobilising local resources in Ethiopia for urban IDPs - Easton-Calabria, E; Abadi, D; Gebremedhin, G (Refugee Studies Centre, University of Oxford, 2020)
Several lessons can be drawn from the successful multi-level response – by both local government and the local community – to the arrival of large numbers of IDPs in Adama, Ethiopia.